2013
DOI: 10.1371/journal.pone.0080181
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Secretion of Plasma Membrane Ca2+-ATPase 4a (PMCA4a) during Murine Estrus: Association with Oviductal Exosomes and Uptake in Sperm

Abstract: PMCA4, a membrane protein, is the major Ca2+ efflux pump in murine sperm where its deletion leads to a severe loss of hyperactivated motility and to male infertility. We have previously shown that the PMCA4b splice variant interacts with CASK (Ca2+/CaM-dependent serine kinase) in regulating sperm Ca2+. More recently we detected that PMCA4a isoform, in addition to its presence in testis, is secreted in the epididymal luminal fluid and transferred to sperm. Here we show that Pmca4 mRNA is expressed in both the 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
202
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(212 citation statements)
references
References 39 publications
8
202
1
1
Order By: Relevance
“…Collection of Oviductal Luminal Fluids from Females after Hormonal Induction of Estrus-Females were induced into estrus as previously described (2,6). Oviductal luminal fluids (OLF) were obtained from 10 superovulated females per experiment.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Collection of Oviductal Luminal Fluids from Females after Hormonal Induction of Estrus-Females were induced into estrus as previously described (2,6). Oviductal luminal fluids (OLF) were obtained from 10 superovulated females per experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Oviductal luminal fluids (OLF) were obtained from 10 superovulated females per experiment. The methodology of collecting the fluid is similar to that described previously (2,6).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most proteins associated with motility are usually located within the mid piece of spermatozoa and BSP proteins have been detected on the mid piece of spermatozoa in several species, which hints at a biological function in the motility of spermatozoa [reviewed in [5]. The motility of spermatozoa is known to be regulated by intracellular calcium signaling molecules, indicating a regulatory function of Ca ?2 -ATPase in spermatozoa motility through this signaling pathway [58]. Further, it was reported that PDC-109 interacts with Ca ?2 -ATPase and enhances the motility of spermatozoa in the bovine model by increasing the pumping efficiency of Ca ?2 -ATPase in an irreversible and cooperative way across the plasma membrane [reviewed in [28].…”
Section: Sperm Motilitymentioning
confidence: 92%